Factors that influence customer retention of using internet banking in Malaysia / Mohamad Shamsul Idham Mohd Salleh - Mohd Salleh, Mohamad Shamsul Idham (2013)
This study is regarding the factors that influence customer retention of using internet banking in Malaysia. It was conducted to identify the factors that influence customer retention of using internet banking service in Malaysia, to investigate the relationship between responsiveness, ease to use, privacy, and assurance (independent variables) of internet banking service with customer retention (dependent variable) of using internet banking service in Malaysia, and to identify the most and least influential factors that influence customer retention of using internet banking service in Malaysia. In this study, 100 questionnaires have been distributed to the respondents which are internet banking users in Kuala Lumpur City Center (KLCC). The researcher has conducted frequency analysis, reliability test, correlation analysis, regression analysis, and descriptive statistic on mean value in order to achieve the objectives of this study. The findings of this study show that the factors that influence customer retention of using internet banking service in Malaysia are responsiveness, ease to use, privacy, and assurance. Besides that, the study also revealed that all independent variables in this study has strong positive and significant relationship with customer retention. In addition, the findings of this study also show that, the most influential factor that influence customer retention of using internet banking service in Malaysia is ease to use while, the least influential factor that influence customer retention of using internet banking service in Malaysia is responsiveness. At the final part of this research report, the researcher has gave recommendations for banking institutions in Malaysia, for customer and for future researcher